Trade and the Development of the Pacific Alliance - Hernández Bernal, José Armando (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2015)
The Pacific Alliance is a process of deep integration among Colombia, Chile, Peru and Mexico, which aims to build a free trade area and to project into the Asia-Pacific region, in order to enhance existing trade agreements among the members. There is no deep trade relationships among these four countries, despite having regional agreements since the 1990s, as demonstrated by the low volume of reciprocal exports and imports, in addition to the low indicator of intra-industrial trade. In this paper, intra-regional trade index is calculated among the countries of the Pacific Alliance, evidencing low indicators, but with a growth, encouraged by reciprocal or unilateral policies of commercial opening, and by an environment favoring economic growth throughout the region.